Bladder cancer prospective cohort study on high‐risk non‐muscle invasive bladder cancer after photodynamic diagnosis‐assisted transurethral resection of the bladder tumor (BRIGHT study). (15th March 2022) - Kobayashi, Keita; Matsuyama, Hideyasu; Kawai, Taketo; Ikeda, Atsushi; Miyake, Makito; Nishimoto, Koshiro; Matsushita, Yuto; Komura, Kazumasa; Abe, Takashige; Kume, Haruki; Nishiyama, Hiroyuki; Fujimoto, Kiyohide; et al.
Abstract : Objectives: Transurethral resection of bladder tumor with photodynamic diagnosis has been reported to result in lower residual tumor and intravesical recurrence rates in non‐muscle invasive bladder cancer. We aimed to evaluate the usefulness of photodynamic diagnosis‐transurethral resection of bladder tumor combined with oral 5‐aminolevulinic acid hydrochloride for high‐risk non‐muscle invasive bladder cancer. Methods: High‐risk non‐muscle invasive bladder cancer patients with an initial photodynamic diagnosis‐transurethral resection of bladder tumor (photodynamic diagnosis group) were prospectively registered between 2018 to 2020. High‐risk non‐muscle invasive bladder cancer cases with a history of initial white‐light transurethral resection of bladder tumor (white‐light group) were retrospectively registered. Propensity score‐matching analysis was used to compare residual tumor rates, and factors that could predict residual tumors at the first transurethral resection of bladder tumor were evaluated. Results: Analyses were conducted with 177 and 306 cases in the photodynamic diagnosis and white‐light groups, respectively. The residual tumor rates in the photodynamic diagnosis and white‐light groups were 25.7% and 47.3%, respectively. Factor analysis for predicting residual tumors in the photodynamic diagnosis group showed that the residual tumor rate was significantly higher in cases with a current/past smoking history, multiple tumors, and pT1/pTis. When each factor was set as a risk level of 1, cases with a total risk score ≤1 showed a significantly lower residual tumor rate than cases with a total risk score ≥2 (8.3% vs 33.3%, odds ratio 5.46 [1.81–22.28]). Conclusions: In high‐risk non‐muscle invasive bladder cancer cases, the odds of a residual tumor after initial photodynamic diagnosis‐transurethral resection of bladder tumor were 0.39‐fold that of the odds of those after initial white‐light transurethral resection of bladder tumor. A risk stratification model could be used to omit the second transurethral resection of bladder tumor in 27% of the cases.